Ventilator-induced diaphragm dysfunction in critical illness. Issue 17 (December 2018) - Liu, Yung-Yang; Li, Li-Fu
Mechanical ventilation is an essential intervention for intensive care unit patients with acute lung injury. However, the use of controlled mechanical ventilation in both animal and human models causes ventilator-induced diaphragm dysfunction, wherein a substantial reduction in diaphragmatic force-generating capacity occurs, along with structural injury and atrophy of diaphragm muscle fibers. Although diaphragm dysfunction, noted in most mechanically ventilated patients, is correlated with poor clinical outcome, the specific pathophysiology underlying ventilator-induced diaphragm dysfunction requires further elucidation. Numerous factors may underlie this condition in humans as well as animals, such as increased oxidative stress, calcium-activated calpain and caspase-3, the ubiquitin–proteasome system, autophagy–lysosomal pathway, and proapoptotic proteins. All these alter protein synthesis and degradation, thus resulting in muscle atrophy and impaired contractility and compromising oxidative phosphorylation and upregulating glycolysis associated with impaired mitochondrial function. Furthermore, infection combined with mechanical stretch may induce multisystem organ failure and render the diaphragm more sensitive to ventilator-induced diaphragm dysfunction. Herein, several major cellular mechanisms associated with autophagy, apoptosis, and mitochondrial biogenesis—including toll-like receptor 4, nuclear factor-κB, Src, class O of forkhead box, signal transducer and activator of transcription 3, and Janus kinase—are reviewed. In addition, we discuss the potential therapeutic strategies used to ameliorate ventilator-induced diaphragm dysfunction and thus prevent delay in the management of patients under prolonged duration of mechanical ventilation. Impact statement: Mechanical ventilation (MV) is life-saving for patients with acute respiratory failure but also causes difficult liberation of patients from ventilator due to rapid decrease of diaphragm muscle endurance and strength, which is termed ventilator-induced diaphragmatic damage (VIDD). Numerous studies have revealed that VIDD could increase extubation failure, ICU stay, ICU mortality, and healthcare expenditures. However, the mechanisms of VIDD, potentially involving a multistep process including muscle atrophy, oxidative loads, structural damage, and muscle fiber remodeling, are not fully elucidated. Further research is necessary to unravel mechanistic framework for understanding the molecular mechanisms underlying VIDD, especially mitochondrial dysfunction and increased mitochondrial oxidative stress, and develop better MV strategies, rehabilitative programs, and pharmacologic agents to translate this knowledge into clinical benefits.